Evaluasi Toleransi Genotipe Kacang Hijau terhadap Cekaman Salinitas - ,, Trustinah; Taufiq, Abdullah; Iswanto, dan Rudi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Salinity has become a serious problem in the production of food crops in Indonesia, especially in coastal areas. Mungbeans is one of commodities which can be grown in coastal areas during the dry season. Research to evaluate tolerance of mungbean genotypes to salinity stress was conducted on saline soil (EC 11.4 dS m-1) at Lohgung Village, Brondong Sub District, Lamongan District during dry season May-July in 2016. A 100 of mungbean genotypes were evaluated using a randomized block design, replicated twice. The majority of the genotypes (82%) were categorized between sensitive to very sensitive to salinity stress. All of the genotypes grew normally to generative phase and produced 2-9 pods per plant with seed yield ranged 0.04-0.60 ton ha-1. The tolerant genotypes had higher plant height, stover weight, and yield than the sensitive genotypes. Six genotypes indicated as very tolerant to salinity stress (EC: 9.24 to 15.06 dS m-1) i.e., MLG 1065/Vima1-279, MMC 464c-gt-4-0-3, MMC 678-8c-gt-5, Vima 1/MLG 1065-286, MLG 1065/Vima1-276 and Vima1/Sampeong//Vima1-249. Seven genotypes indicated as tolerant to salinity stress i.e., Vima1/MLG1065-290, MLG1065/Vima1-272,  MLG1065/Vima1-274, Vima1/MLG 1065-287, Vima1/MLG 1065-276, MMC 267c-mn-1-1-11, and VIMA 1/MLG 1065-288. These selected genotypes were potential to be developed into new mungbean variety tolerant to salinity.Keywords: electrical conductivity, growth, yield, selection, Vigna radiata